A rare case of primary female urethral adenocarcinoma: Columnar type with colonic adenocarcinoma features - Prithal Gangadhar; Muktha R Pai; I Sandhya (Wolters Kluwer Medknow Publications, 2018)
Female urethral carcinoma is extremely rare and accounts for 0.02% of all women's cancers and <1% of cancers in the female genitourinary tract. Adenocarcinoma accounts for only 10% of urethral carcinomas in females. Due to their location, presentation is usually late and tumors are often missed on physical examination. As in this case, nonspecific symptoms in the early stages may delay the diagnosis in most patients. Herein, we present an extremely rare case of the columnar type of primary female urethral adenocarcinoma exhibiting colonic adenocarcinoma features which to the authors' best knowledge has not been reported to date. The present study emphasizes the importance of a careful clinical examination and also highlights the role of imaging studies, and biopsy in making an accurate preoperative diagnosis of this rare disease. The disease may have devastating sequelae due to local and metastatic involvement if not recognized and treated earlier.